1996
DOI: 10.1111/j.2042-3306.1996.tb03111.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Accusport for measurement of lactate concentrations in equine blood and plasma

Abstract: Summary The aim of this study was to investigate correlations between lactate concentrations in equine whole blood and plasma measured with Accusport1 and Yellow Springs Instruments (YSI2) (2300) methods. The effect of packed cell volume (PCV) on the accuracy of Accusport was also investigated. Blood samples were collected from Thoroughbred horses at 5–10 min intervals after a treadmill exercise test. Blood was added to NaEDTA (for PCV measurement) and to 2 tubes containing lithium heparin anticoagulant (for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
56
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 7 publications
4
56
0
1
Order By: Relevance
“…23,25 Some of these same monitors have been evaluated in healthy, exercising horses and have been shown to be useful. [20][21][22] However, aside from a relatively small study in horses with colic, 24 the utility of these devices in abnormal horses has not been assessed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…23,25 Some of these same monitors have been evaluated in healthy, exercising horses and have been shown to be useful. [20][21][22] However, aside from a relatively small study in horses with colic, 24 the utility of these devices in abnormal horses has not been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to the findings of some earlier reports examining the accuracy and reliability of the same POC monitor in exercising Thoroughbred horses. [20][21][22] In 1 study, the monitor's accuracy was compared with a well-accepted reference technique that used linear regression analysis. 20 Good association was found between whole blood measurements on the Accutrend and reference technique but only for lactate concentrations ,10 mM and PCV ,53%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In horses, blood lactate has been measured during treadmill tests [14,18] and running tests under field conditions [5,9]. It has been reported that the Accusport (AC) portable analyzer should be used only to measure lactate concentration in equine whole blood when Ht is less than 53% and lactate concentration is less than 10 mmol/l [4].…”
mentioning
confidence: 99%